Design and Implementation of a Secure Communication Protocol - M. K. Viswanath; M. Ranjith Kumar (Institute of Advanced Engineering and Science, 2018)
The main object of this paper is to present a mutual authentication protocol that guarantees security, integrity and authenticity of messages, transferred over a network system. In this paper a symmetric key cryptosystem, that satisfies all the above requirements, is developed using theorems of J.R. Chen, I.M. Vinogradov and Fermat and the decimal expansion of an irrational number.